2001
DOI: 10.2337/diacare.24.4.695
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Care Clinics for Diabetes in Primary Care

Abstract: OBJECTIVE -To evaluate the impact of primary care group visits (chronic care clinics) on the process and outcome of care for diabetic patients.RESEARCH DESIGN AND METHODS -We evaluated the intervention in primary care practices randomized to intervention and control groups in a large-staff model health maintenance organization (HMO). Patients included diabetic patients Ն30 years of age in each participating primary care practice, selected at random from an automated diabetes registry. Primary care practices we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
378
2
5

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 349 publications
(389 citation statements)
references
References 23 publications
(24 reference statements)
4
378
2
5
Order By: Relevance
“…Wagner, in a study of 707 diabetic patients, reported that group visit participation was positively associated with subjects receiving preventive procedures, having medications reviewed, and having a microalbuminuria test recorded in the diabetes registry. 42 Similarly, Clancy found that diabetic patients participating in group visits demonstrated improvement in 10 American Diabetes Association processes of care indicators. 30 -32 A study by Sadur showed that poorly controlled diabetics (average HbA1C greater then 8.5%), who attended group visits significantly increased intake of insulin, sulfonylureas, and metformin compared with controls, 35 whereas another study of relatively well-controlled type 2 diabetic patients attending group visits demonstrated lowered dosage of hypoglycemic agents than in standard care.…”
Section: Quality Of Carementioning
confidence: 99%
See 2 more Smart Citations
“…Wagner, in a study of 707 diabetic patients, reported that group visit participation was positively associated with subjects receiving preventive procedures, having medications reviewed, and having a microalbuminuria test recorded in the diabetes registry. 42 Similarly, Clancy found that diabetic patients participating in group visits demonstrated improvement in 10 American Diabetes Association processes of care indicators. 30 -32 A study by Sadur showed that poorly controlled diabetics (average HbA1C greater then 8.5%), who attended group visits significantly increased intake of insulin, sulfonylureas, and metformin compared with controls, 35 whereas another study of relatively well-controlled type 2 diabetic patients attending group visits demonstrated lowered dosage of hypoglycemic agents than in standard care.…”
Section: Quality Of Carementioning
confidence: 99%
“…35 Wagner's investigation of diabetic patients demonstrated lower frequency of specialty and emergency department visits, but no significant differences in primary care visits (which approached significance), hospitalization frequency, rates of foot and retinal exams, or medication reviews. 42 Maizels reported that a group visit intervention designed for chronic headache resulted in dramatically lower outpatient and emergency department utilization, although significance was not assessed. 44 The study done by Blumenfeld and Tischio of a group visit program for headache also reported decreased primary care visits, emergency visits, and CT scans, but neurology visits and use of injected and oral narcotics increased.…”
Section: Health Service Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are not surprising in light of findings from a number of large managed care organizations using group appointments for chronic disease management. They have found not only lower costs [27][28][29] and reduced utilization [27,[29][30][31] but also improved patient satisfaction [27,[31][32][33], self-efficacy [29,31], health status, [28,31,[33][34][35][36][37][38], compliance [39], and quality of life (QOL) [29]. For example, in a randomized trial comparing group versus individual outpatient visits for patients with a variety of chronic illnesses, patients treated in group appointments had fewer emergency room and subspecialty visits, fewer hospital admissions, greater patient and provider satisfaction, and lower overall costs [27].…”
Section: In This Nonrandomized Retrospective Chart Review Of New Hearmentioning
confidence: 99%
“…To accomplish this mission, the MSCoE West is implementing a model of care adapted from other chronic-care models that have been successful in managing large populations with chronic diseases such as diabetes and asthma [1][2]. Wagner and colleagues have described a system approach to the care of populations with chronic disease that is built around two essential elements: (1) "prepared, proactive, practice teams" that use tools such as evidence-based guidelines, data repositories, and an electronic medical record (EMR) to manage high-risk groups with specific conditions and (2) "an educated and empowered patient" who receives education and training and is an active participant in his or her healthcare [3][4].…”
Section: Introductionmentioning
confidence: 99%